Health Risk Behaviours Among Adolescents in Schools of Kavre - Budhathoki, Bamita; Chettri, Poonam Khadka; Shrestha, Rhinu; Karmacharya, Sanskriti (Journal of Manmohan Memorial Institute of Health Sciences, 2024)
Background: Health risk behaviors is increasing as a serious health threat and alarming issue in worldwide. The objective of the study was to find out the health risk behaviors among adolescents in schools of Kavre.Method: A descriptive cross-sectional design was carried out among 110 adolescent’s students in schools of Kavre using non-probability purposive sampling technique. Data was collected through self-administered questionnaire technique by using Global School Based Student Health Survey tool and analyzed by descriptive statistics using SPSS 25.Results: More than half (54.5%) of adolescents were seriously injured where Only (18.5%) of them were physically attacked, less than half (31.8%) were involved in physical fight. Only 6.4% of them had sexual intercourse. Nearly half (41.4%) of them were current alcohol user and Half (50.0%) of them smoked cigarettes. Among them 20 % of them first drank alcohol, 10.9% of them first smoked at age before 14 years. Less than half (31.8 %) of them didn’t involve in physical activity. Only 7.3% and 6.4% of them didn’t eat fruits and vegetables. Most (79.1%) of them consumed fast food.Conclusion: Regarding health risk behaviours more than half of the adolescent students engage in unintentional injury. Few of them involve in sexual behaviours. Nearly half of them are current alcohol and cigarette smoker. Less than half of the adolescent’s student aren’t involve in physical activity. Most of them prefer fast food. Thus, health promoting behaviors can be planned and organized in a school for adolescents’ student.